1994
DOI: 10.1111/j.1600-0765.1994.tb01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long‐term methotrexate‐induced neutropenia on experimental periodontal lesion in rats

Abstract: The effects of long-term methotrexate (MTX)-induced neutropenia on the periodontal lesion in rats were investigated histologically, histometrically and bacteriologically. A nylon thread was inserted into the interdental gingiva between the 1st and 2nd right maxillary molars of the animals 3 weeks before an application of MTX. The animals were then divided into Groups A and B. Group B were injected intraperitoneally with 1.0 mg/kg of MTX 3 times per week for 9 weeks. Group A received saline as a control. Five a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 22 publications
1
22
0
1
Order By: Relevance
“…51,52 Long-term use of methotrexate in rats with PD enhanced alveolar bone destruction. 53 Glucocorticoids may have induced osteoporosis, 54 and this therapy may also delay wound healing and increased risk of gingival infection, 28 however the effect of this medication in alveolar bone is unknown in JIA. Despite the immunosuppressive treatment, the majority of JIA patients presented mild gingivitis without loss of connective tissue attachment, and periodontitis was rarely described.…”
Section: Juvenile Idiopathic Arthritis (Jia)mentioning
confidence: 99%
“…51,52 Long-term use of methotrexate in rats with PD enhanced alveolar bone destruction. 53 Glucocorticoids may have induced osteoporosis, 54 and this therapy may also delay wound healing and increased risk of gingival infection, 28 however the effect of this medication in alveolar bone is unknown in JIA. Despite the immunosuppressive treatment, the majority of JIA patients presented mild gingivitis without loss of connective tissue attachment, and periodontitis was rarely described.…”
Section: Juvenile Idiopathic Arthritis (Jia)mentioning
confidence: 99%
“…Loss of the protective neutrophilic barrier function either by congenital deficiency (Page et al ., 1987; Waldrop et al ., 1987; Carrassi et al ., 1989; Hart et al ., 1994) or by chemical induction with antimitotic agents such as cyclophosamide (Attström and Schroeder, 1979; Sallay et al ., 1984; Hemmerle and Frank, 1991; Yoshinari et al ., 1994) invariably leads to disease. Further, studies have shown that the lack of an intact innate host defense system may be responsible for the significantly increased incidence of severe periodontitis observed in diabetic patients (type I and type II) and tobacco users (Bergstrom et al ., 1988; MacFarlane et al ., 1992; Offenbacher et al ., 1996; Zambon, 1996; Salvi et al ., 1997).…”
Section: Innate Host Defense Status In Clinically Healthy and Diseasementioning
confidence: 99%
“…Individuals that have congenital deficiencies in either neutrophil numbers (Attström and Schroeder 1979;Page et al 1987;Carrassi et al 1989;Hart et al 1994;Deas et al 2003;Hajishengallis et al 2015) or transit (leukocyte adhesion deficiency 1 and 2) or have an induced neutropenia by chemical induction with antimitotic agents such as cyclophosamide (Attström and Schroeder 1979;Sallay et al 1984;Hemmerle and Frank 1991;Yoshinari et al 1994) can develop periodontitis. Likewise, studies have shown that knockout mice that are defective in neutrophil transit also develop periodontitis (Niederman et al 2001;Yu et al 2007;Hajishengallis et al 2011).…”
Section: Introductionmentioning
confidence: 99%